Radiocarbon and thermogravimetric analysis (TGA) results of permafrost leachate from the Lena Delta, Arctic - Tsai-Wen Lin; Gernot Nehrke; Hendrik Grotheer; Boris P Koch; Gesine Mollenhauer (PANGAEA, 2025)
This datasheet includes radiocarbon and thermogravimetric analysis (TGA) results of permafrost leachate from samples collected in the Lena Delta. The leaching protocol followed Ksionzek et al. (2018). Around 200 mg of dried sediment was leached in 20 mL deionized water for 24 hours at 4 °C, with intermittent shaking every 6-8 hours. The leachates were filtered through 0.7 μm GF/F filters, acidified to pH 2 using 37% HCl, and analyzed by high-temperature catalytic combustion (Shimadzu, TOC-VCPN). Pretreatment and measurement of radiocarbon analysis followed protocols in Mollenhauer et al. (2021). Freeze-dried leachates were wrapped into silver boats and converted into graphite targets using Elementar vario Isotope coupled to Ionplus AG, AGE-3. Radiocarbon isotopic ratios were measured using MICADAS at AWI, Bremerhaven. For TGA analysis, leachate samples of ~10 mg were analyzed in 70 μL aluminum oxide crucibles using a Mettler Toledo TGA/DSC 1. The samples were heated from 25 to 1000 °C at a rate of 10 °C min-1 under a constant argon flow of 20 mL min-1, following similar settings from Smeaton & Austin (2022). Following Lopez-Capel et al. (2006), weight loss between 200–400 °C is attributed to the decomposition of labile organic matter (OML), while weight loss between 400–650°C corresponds to the decomposition of recalcitrant and refractory organic matter (OMR). The percentage of labile organic matter (OML/OM) is calculated as [OML/(OML+OMR)]*100%
In: Lin, Tsai-Wen; Nehrke, Gernot; Mollenhauer, Gesine (2025): Bulk organic matter data of Lena Delta permafrost, marine surface sediment, and sediment cores from the Laptev Sea, Arctic Ocean [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984732